2010
DOI: 10.1007/978-1-4419-6199-0_3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Cytokinesis Failure

Abstract: Cytokinesis is the final step in cell division. The process begins during chromosome segregation, when the ingressing cleavage furrow begins to partition the cytoplasm between the nascent daughter cells. The process is not completed until much later, however, when the final cytoplasmic bridge connecting the two daughter cells is severed. Cytokinesis is a highly ordered process, requiring an intricate interplay between cytoskeletal, chromosomal, and cell cycle regulatory pathways. A surprisingly broad range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
137
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(148 citation statements)
references
References 317 publications
10
137
0
1
Order By: Relevance
“…[56][57][58] Cytokinesis failure leads to centrosome amplification and production of tetraploid cells, introducing chromosomal instability and setting the stage for tumor cell development. 23,32 Expression of TPC1 was significantly upregulated in a human protein array of tumor tissue compared to normal tissue, suggesting that dysregulated TPC1 expression may contribute to the aberrant cell division prominent in many cancers. Furthermore, CIT is frequently upregulated in hepatocellular carcinoma, 37 further highlighting the role of abscission control in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[56][57][58] Cytokinesis failure leads to centrosome amplification and production of tetraploid cells, introducing chromosomal instability and setting the stage for tumor cell development. 23,32 Expression of TPC1 was significantly upregulated in a human protein array of tumor tissue compared to normal tissue, suggesting that dysregulated TPC1 expression may contribute to the aberrant cell division prominent in many cancers. Furthermore, CIT is frequently upregulated in hepatocellular carcinoma, 37 further highlighting the role of abscission control in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A number of additional cellular processes are also important in cytokinesis, including protein and membrane trafficking, lipid metabolism, protein synthesis and DNA damage. 23 Dys-regulation of this process can cause multinucleation and aneuploidy, processes that can lead to chromosomal instability and directly impact cancer progression. [24][25][26] Successful partitioning of cytoplasmic and genomic materials at the end of cell division requires a transition from constriction to abscission and interaction between contractile ring and spindle components, but how these events are coordinated is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Each stage is dependent on the proper execution of the prior stage; thus, interference with any stage may result in cytokinesis failure (39). In the liver, cytokinesis failure occurs as a result of the absence of actin cytoskeleton organization at the cleavage plane.…”
Section: Discussionmentioning
confidence: 99%
“…Pohl and Jentsch (2008) reported that the depletion of BRUCE, which processes ubiquitinconjugating activity, causes defective abscission and cytokinesis-associated apoptosis, accompanied by a blockage of vesicular targeting as well as defective formation of the midbody and midbody ring. Inactivation or hyperactivation of several of these factors was shown to induce cytokinesis failure, resulting in the inhibition or regression of the cleavage furrow with the formation of tetraploid cells or the persistence of connections between daughter cells with the formation of long intercellular bridges (LIBs) and syncytial cells (Normand and King 2010). Morizur et al (2010) suggested that polyploidy including binucleated cells may protect hepatocytes from genotoxic damage by increasing their gene copy number, and may prolong cell survival from apoptosis.…”
Section: Discussionmentioning
confidence: 99%